2011
DOI: 10.1097/tp.0b013e31821cdf0d
|View full text |Cite
|
Sign up to set email alerts
|

Pretransplant IgG Subclasses of Donor-Specific Human Leukocyte Antigen Antibodies and Development of Antibody-Mediated Rejection

Abstract: In 90% of patients, pretransplant HLA-DSA are composed of isolated strong or a mixture of strong and weak/no complement-activating IgG subclasses. Because outcomes in these two groups were similar, pretransplant IgG subclass analysis is likely not providing substantial value beyond the standard IgG SAFB assay for pretransplant risk stratification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
91
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(99 citation statements)
references
References 21 publications
7
91
1
Order By: Relevance
“…Our data confirm previous studies showing that IgG1 represents the predominant anti-HLA DSA subclass reported in the solid organ transplantation literature, which is variably associated with the other IgG subclasses (IgG2, 3, and 4). 12,[22][23][24][25][26][27][28] The initial appearance of strong complementfixing IgG1 and IgG3 antibodies may expand to weak or noncomplement-binding IgG2 and IgG4 antibodies; therefore, various profiles of IgG subclasses are seen in transplant recipients. 29 Previous studies have failed to firmly identify a predictive subclass pattern due to the heterogeneous IgG subclass response and to several technical [30][31][32] and methodological limitations, mainly related to the small number of recipients included 26,33,34 or the lack of precise clinical and histologic phenotyping of the ABMR injury.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our data confirm previous studies showing that IgG1 represents the predominant anti-HLA DSA subclass reported in the solid organ transplantation literature, which is variably associated with the other IgG subclasses (IgG2, 3, and 4). 12,[22][23][24][25][26][27][28] The initial appearance of strong complementfixing IgG1 and IgG3 antibodies may expand to weak or noncomplement-binding IgG2 and IgG4 antibodies; therefore, various profiles of IgG subclasses are seen in transplant recipients. 29 Previous studies have failed to firmly identify a predictive subclass pattern due to the heterogeneous IgG subclass response and to several technical [30][31][32] and methodological limitations, mainly related to the small number of recipients included 26,33,34 or the lack of precise clinical and histologic phenotyping of the ABMR injury.…”
Section: Discussionmentioning
confidence: 99%
“…29 Previous studies have failed to firmly identify a predictive subclass pattern due to the heterogeneous IgG subclass response and to several technical [30][31][32] and methodological limitations, mainly related to the small number of recipients included 26,33,34 or the lack of precise clinical and histologic phenotyping of the ABMR injury. 23,24 The integration of different properties of circulating anti-HLA DSA, including HLA class specificity, strength, complementbinding capacity and IgG subclasses, allowed us to identify three distinct clinical and histologic patterns of antibody-mediated injury, as recognized by the latest Banff classification: aABMR, sABMR, and ABMR-free. 35 The unsupervised PCA allowed us to hierarchically rank the variables that characterize these different patterns of antibody-mediated injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8][9] Because a fraction of dnDSA-positive patients escape rejection or graft dysfunction, 9,13 the current challenge is to identify clinically relevant dnDSAs in order to better stratify the individual immunologic risk. Several proposed approaches rely on serum dnDSA SAFB mean fluorescence intensity (MFI) strength, 14,15 IgG subclass analysis, 16 or complement-binding ability. 17,18 DSAs are deleterious via different pathways, but complement C4d deposition in peritubular capillaries reflects the central role of complement in AMR endothelial cell aggression.…”
mentioning
confidence: 99%
“…The subclass repertoire is potentially more informative for assessing the pathogenicity of DSAs than complement assays, as subclass predicts complement activation, Fcγ receptor-dependent (FcγR-dependent) functions, and the immunobiology of the alloantibody response. A growing number of reports suggest that characterization of DSA IgG subclass may have utility in identifying patients at risk of rejection or graft loss (5, [55][56][57][58][59][60]. While enlightening, these studies have yet to capture the impact of mixtures of subclasses or multiple concurrent DSA specificities.…”
Section: Neutrophil Marginationmentioning
confidence: 99%